Mazabraud's Syndrome Mimicking Metastases on FDG PET/CT in a Patient With Colon Cancer. (August 2018) - Mahajan, Sonia; Goel, Reema; Riedl, Christopher; Ulaner, Gary A.
Abstract : Abstract: Mazabraud's, a syndrome consisting of fibrous dysplasia and soft tissue myxomas, is a rare disorder with less than 100 cases reported in the literature. Appearance of lesions in Mazabraud's syndrome on FDG PET/CT scan in an oncological scenario can be misinterpreted as malignancy. We present the case of a 69-year-old woman, diagnosed with metastatic colon carcinoma and suspected osseous as well as soft tissue metastases, who was later found to have concomitant Mazabraud's syndrome. This case describes the diagnostic dilemma associated with this unusual entity and importance of differentiating benign and malignant etiologies on FDG PET/CT scan.